Strategies of Production in the Automobile Industry: a Multi-Case Study in Spain and Brazil - Vanalle, Rosangela Maria; Salles, José Antonio Arantes; Vieira Junior, Milton (Brazilian Journal of Operations & Production Management, 2010)
The aim of this paper is to identify and to analyze the manufacturing strategies of two supply chains of the automobile industry and the assemblers’ influences on the other participants in each chain. Two plants of the same assembler, one in Brazil and the other in Spain and their suppliers, were analyzed, using questionnaires and interviews. It was observed that the competitive priorities of the suppliers are strongly conditioned to the strategy of the assembler, and the ordination of these priorities in the Brazilian case is different from that in the Spanish case. One of the reasons of this difference in the ordination of priorities of the Brazilian and the Spanish companies can be explained by the traditional competitive capabilities for exporting of the Spanish automotive industry, which inserts in the world market a larger percentile of production than the Brazilian industry. Even so it can be confirmed that in Brazil and Spain the inter-business relationships are suffering a transition of mass production, with conflicting relationships supplier-manufacturer, for a relationship of larger cognitive density, characteristic of the presuppositions of organization of supplies based on the model flexible production or lean manufacturing.